Effects of crenolanib, a nonselective inhibitor of PDGFR, in a mouse model of transient middle cerebral artery occlusion. (19th November 2017) - Wang, Jianping; Fu, Xiaojie; Zhang, Di; Yu, Lie; Lu, Zhengfang; Gao, Yufeng; Liu, Xianliang; Man, Jiang; Li, Sijia; Li, Nan; Wang, Menghan; Liu, Xi; et al.
Highlights: We used crenolanib to study the role of PDGFR pathway in MCAO mice. Crenolanib interfered with migration and survival of neuroblasts from SVZ to infarction. Crenolanib decreased angiogenesis and chemo-attractants secretion in MCAO mice. Crenolanib activated microglia and decreased neuroprotectants' level in MCAO mice. Crenolanib accelerated the apoptosis of pericytes in the peri-infarct area in MCAO mice. Abstract: Neurogenesis in the subventricular zone (SVZ) plays a vital role in neurologic recovery after stroke. However, only a small fraction of newly generated neuroblasts from the SVZ will survive long-term. Successful migration and survival of neuroblasts requires angiogenesis, lesion-derived chemo-attractants, and appropriate local microenvironments, which are partly regulated by the platelet-derived growth factor receptor (PDGFR) signaling pathway. In this study, we investigated the effects of PDGFR inhibition in a mouse model of transient middle cerebral artery occlusion (MCAO). We blocked the pathway using a nonselective PDGFR inhibitor, crenolanib, during the acute post-MCAO phase (days 1–3) or during the sub-acute phase (days 7–9). Downregulating the PDGFR signaling pathway with crenolanib from day 1 to day 3 after MCAO significantly decreased the migration of neuroblasts from the SVZ to the peri-infarct region, decreased angiogenesis, and lowered expression of vascular endothelial growth factor, stromal cell-derived factor-1, and monocyte chemotactic protein-1. Downregulation of the PDGFR signaling pathway on days 7–9 with crenolanib significantly increased apoptosis of the neuroblasts that had migrated to the peri-infarct region, increased the number of activated microglia, and decreased the expression of brain-derived neurotrophic factor, neurotrophin-3, and interleukin-10. Crenolanib treatment increased the apoptosis of pericytes and decreased the pericyte/vascular coverage, but had no effects on apoptosis of astrocytes. We conclude that the PDGFR signaling pathway plays a vital role in the SVZ neurogenesis after stroke. It can also affect angiogenesis, lesion-derived chemo-attractants, and the local microenvironment, which are all important to stroke-induced neurogenesis.